The Merrybegot - Hearn, Julie, 1958- (Oxford : Oxford University Press, 2011)
In 1645 in England, the daughters of the town minister successfully accuse a local healer and her granddaughter of witchcraft to conceal an out-of-wedlock pregnancy, but years later during the 1692 Salem trials their lie has unexpected repercussions.
Keywords: Hopkins, Matthew, -- d. 1647 -- Fiction; Fairies -- Fiction; Pregnancy -- Fiction; Sisters -- Fiction; Supernatural -- Fiction; Trials (Witchcraft) -- Fiction; Witchcraft -- Fiction; Great Britain -- History -- Civil War, 1642-1649 -- Fiction; Salem (Mass.) -- History -- Colonial period, ca. 1600-1775 -- Fiction; Somerset (England) -- History -- Civil War, 1642-1649 -- Fiction